فاعلیة استخدام التعلیم المدمج في تدریس العلوم في مستوى تحصیل تلامیذ الصفوف الأولى بالمرحلة الابتدائیة بمحافظة الكرك - الختاتنة، میسون كریم فلاح Alkhattatneh, Mayson Karim Fallah (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2018)
هدفت الدراسة تعرف فاعلية استخدام التعليم المدمج في تدريس العلوم على مستوى تحصيل تلاميذ المرحلة الابتدائية، واتبعت الدراسة المنهج شبه التجريبي حيث تم تطبيق اختبار تحصيلي على مجموعتين من تلاميذ الصف الصفوف الأولى في مادة العلوم الأولى تم تدريسها بالطريقة الاعتيادية والمجموعة الثانية تم تدريسها بطريقة التعليم المدمج، وقد توصلت الدراسة إلى نتائج أهمها وجود فاعلية للتعليم المدمج في مستوى تحصيل تلاميذ الصف الصفوف الأولى في مادة العلوم حيث تبين وجود فروق دالة إحصائيا لصالح المجموعة التجريبية التي تم تدريسها بطريقة التعليم المدمج. وعلى ضوء النتائج أوصت الباحثة بضرورة توفير البينة المناسبة للتعليم المدمج بما يحسن من المخرجات التعليمية وبرقع مستوى التحصيل التعليمي لدى تلاميذ الصف الصفوف الأولى في مادة العلوم، من خلال توفير البرامج والتطبيقات التعليمية المهمة للتعليم.
The study aimed at shed light on the reality of the practice of blended teaching of science in the first grades of schools, and to identify its impact on improving the level of education achievement among the first grade students in science. The study followed the semi-experimental method. An attainment test was applied on two groups of first grade students in science subject, the first group taught in the usual teaching method and the second group was taught using blended teaching method. The study found that blended teaching was effective in improving the level of achievement of the first grade students in the science, where there were significant differences for in improving of the experimental group, which was taught in a blended learning method In the light of the results, the researcher recommended the need to provide the appropriate environment for blended teaching in order to improve the educational outcomes and the level of educational attainment of the first grade students in science by providing educational programs and applications for education.
Keywords: تدریس العلوم; التحصیل الدراسى; المرحلة الابتدائیة; التعلیم المدمج; محافظة الكرك